PERLINDUNGAN HUKUM TERHADAP NASABAH YANG MENGALAMI KERUGIAN AKIBAT KESALAHAN SISTEM BANK DALAM LAYANAN MOBILE BANKING - Muhammad Daffa Ghifari (Fakultas Hukum Universitas Udayana, 2023)
The aim of this study is to examine the risks that can occur in the use of m-banking, which is currently being widely used as a means of payment and legal protection by customers when undesirable consequences (losses) occur, both material and immaterial. This study was carried out using normative legal research methods with a statue approach (legislative approach) and a case approach (case approach). The study results show that banking services in the form of mobile banking carry risks in the form of material losses, namely cyber crime, both in the form of phishing and MIB, transaction failures and repeated transactions, as well as taking over mobile phone numbers and confiscation of mobile banking PINs. Then legal protection for banking consumers/customers can be provided in a preventive and repressive manner. The regulations can be seen in several applicable laws, namely the Banking Law, Fund Transfer Law, Bank Indonesia Consumer Protection PERBI, POJK Consumer and Community Protection in the Financial Services Sector, POJK Information Technology Implementation by Commercial Banks, and POJK Consumer Complaint Services in In the financial services sector, if a loss occurs, a customer can make a complaint to the bank and if they object to the results given, the customer can complain to Bank Indonesia or file a lawsuit, either through alternative dispute resolution institutions or the courts.